Listeria monocytogenes endocarditis. Issue 711 (January 1985) - Sheinman, B. D.; Evans, T.; Sage, R.
Abstract : A fatal case of endocarditis due to Listeria monocytogenes is reported. Case reports of endocarditis due to this organism are rare but indicate a higher mortality than with many other causes of bacterial endocarditis. The size of the problem may be underestimated because the organism has a "diphtheroid' appearance and may be incorrectly dismissed as a contaminant.